2023
DOI: 10.1038/s41598-023-32212-4
|View full text |Cite
|
Sign up to set email alerts
|

A temporal single cell transcriptome atlas of zebrafish anterior segment development

Abstract: Anterior segment dysgenesis (ASD), resulting in vision impairment, stems from maldevelopment of anterior segment (AS) tissues. Incidence of ASD has been linked to malfunction of periocular mesenchyme cells (POM). POM cells specify into anterior segment mesenchyme (ASM) cells which colonize and produce AS tissues. In this study we uncover ASM developmental trajectories associated with formation of the AS. Using a transgenic line of zebrafish that fluorescently labels the ASM throughout development, Tg[foxc1b:GF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 105 publications
0
6
0
Order By: Relevance
“…We were able to compare our data to human studies (van Zyl et al, 2020;van Zyl et al, 2022) and found that human marker genes such as krt4, krt5 and myoc are expressed in the zebrafish cornea and AL respectively. Moreover, we found previously unknown markers like hgd and cndp1 expressed in the AL which might also play a role in human TM development (Vöcking and Famulski, 2023). This kind of multiple time point analyses enables the exact determination of the genetic profile of cells during their development and help identify critical moments of their differentiation (Figure 2C) (also see Farnsworth et al, 2020;Farnsworth et al, 2021).…”
Section: Zebrafish Developmental Single Cell Transcriptome Applicatio...mentioning
confidence: 59%
See 4 more Smart Citations
“…We were able to compare our data to human studies (van Zyl et al, 2020;van Zyl et al, 2022) and found that human marker genes such as krt4, krt5 and myoc are expressed in the zebrafish cornea and AL respectively. Moreover, we found previously unknown markers like hgd and cndp1 expressed in the AL which might also play a role in human TM development (Vöcking and Famulski, 2023). This kind of multiple time point analyses enables the exact determination of the genetic profile of cells during their development and help identify critical moments of their differentiation (Figure 2C) (also see Farnsworth et al, 2020;Farnsworth et al, 2021).…”
Section: Zebrafish Developmental Single Cell Transcriptome Applicatio...mentioning
confidence: 59%
“…With the help of fluorescent activated cell sorting (FACS), non-fluorescent cells can simply be sorted out, which allows the use of only the specifically desired cell type for the analysis. This method has already been applied successfully to isolate various neural crest cells including those forming the anterior segment, but also retinal cells, immune cells and cells of the developing gonads among others (see Figure 1) (Carmona et al, 2017;Hernandez et al, 2018;Zhang et al, 2019;Van Der Meulen et al, 2020;Howard et al, 2021;Tatarakis et al, 2021;Liu et al, 2022;Vöcking and Famulski, 2023). Hence, the dissection of the fragile tissue can be avoided altogether.…”
Section: Precise Tissue Collectionmentioning
confidence: 99%
See 3 more Smart Citations